Effects of financial development, FDI and good governance on environmental degradation in the Arab nation: Dose technological innovation matters? - Ju, Shuwen; Andriamahery, Anselme; Qamruzzaman, Md; Kor, Sylvia (Frontiers in Environmental Science, 2023)
The motivation of the study is to gauge the impact of financial development, FDI, Technological innovation, and good governance on environmental degradation in the Arab Nation for the period 1991–2019. Several techniques have implemented, including error correction-based cointegration, cross-sectional ARDL, Non-linear ARDL and Heterogeneous causality test for directional causality. The results of Slope of homogeneity, CSD and unit root test following CIPS and CADF, revealed that research variables are exposed with heterogeneity properties, cross-sectionally dependent, and all the variables become stationary after the first difference. The long-run cointegration between explained and explanatory variables established through error correction based cointegrating test. Referring to results derived from CS-ARDL, study exposed financial development has a detrimental effect on environmental sustainability, suggesting the intensification of CO2 emission and ecological instability. On the other hand, the role of FDI, GG, and TI exposed beneficiary in mitigating the environmental adversity. The asymmetric assessment revealed asymmetric association between explained and core explanatory variables which is valid in the long-run and short-run horizon. Finally, the casual association, study unveiled bidirectional causality between FDI, TI and ED [FDI←→ED; TI←→ED]. On the policy note, the study advocated that environmental improvement through financial channels should be efficiently monitored in the case of credit extension and incorporation with existing environmental policies.